Povej mi, kako si? (University of Maribor Press, 2019)
Tell Me, How are You? Depression is one of the most common illnesses of mental health and it is becoming more important in everyday life, because the prevalence for the depression is rising. The monograph: Tell me, how are you? is a work, done by a project group of students from University of Maribor, which researched depression with partners from local community Hoče-Slivnica. The goal of the project was to make depression more aware and to lessen the stigmatization of mental illnesses. We wrote about medical, psychological, sociological, economy and legal views of depression, that are important for early discovering of the illness and for future changes, which could lessen the stigmatization. We have included examples of good practices and suggestions for improving individuals’ wellbeing. The most important factor in the battle against depression is social support and interpersonal relationships, so at least we can do, is ask someone: Tell me, how are you?